Use of artificial intelligence in legislation: organizational and legal aspects - Kuttybaeva, A.K. (Bulletin of the Karaganda University “Law Series”, 2024)
The purpose of the article is to analyze the key legal and organizational aspects of integrating AI into lawmaking and to identify the main challenges and opportunities. The article aims to provide recommendations for the effective implementation of AI in legislative processes, based on international experience and specific problems. The following methodological approaches were used in the study: comparative legal analysis, qualitative analysis, and sociological method. Comparative legal analysis allowed us to identify both differences and similarities in the use of artificial intelligence (AI) in legislative processes in various jurisdictions. Qualitative analysis was used for an in-depth study of scientific literature and legal documents, which helped to identify key trends and issues in this area. The sociological method was used to assess the impact of AI on the level of citizen engagement and perception of legislative processes. The article emphasizes that although AI can improve the effectiveness of legislative activity, the introduction of AI raises serious concerns related to the change in the traditional role of legislators and possible bias of algorithms. Additionally, natural language processing technologies are explored as an organizational tool for improving the quality of legislative texts. The study identified key legal and organizational aspects of the integration of artificial intelligence (AI) into lawmaking processes that are actively developing in the world. The paper provides examples of such countries as China, Estonia, Italy, Denmark and South Africa, illustrating the pluralism of approaches to the implementation of AI in legislative activity. In this regard, the article covers the importance of human oversight to ensure legal consistency and eliminate potential risks associated with the use of AI in the lawmaking process